Eocene palms from central Myanmar in a South-East Asian and global perspective: evidence from the palynological record. (15th July 2020) - Huang, Huasheng; Morley, Robert; Licht, Alexis; Dupont-Nivet, Guillaume; Grímsson, Friðgeir; Zetter, Reinhard; Westerweel, Jan; Win, Zaw; Wa Aung, Day; Hoorn, Carina
Abstract: In the Palaeogene, pollen assemblages at low and mid latitudes are characterized by abundant palm and palm-like (PPL) taxa. Although these taxa have been widely reported, their occurrence in the Palaeogene of Myanmar remains poorly documented. Here we report on the morphology of PPL pollen along a middle to upper Eocene sedimentary sequence in central Myanmar and discuss their nearest living relatives (NLRs). Principal components analysis (PCA) indicates that Palmaepollenites kutchensis, Dicolpopollis and Longapertites were dispersed from freshwater plants, whereas the parent taxon of Proxapertites operculatus was probably a member of the coastal vegetation in the manner of Spinizonocolpites . This, with sedimentological data, suggests a palaeoenvironmental change from a brackish, tidally influenced environment to a fully freshwater setting through the late Eocene. Additionally, we mapped and compared the geographical distribution of selected Eocene palm taxa and their NLRs, and found that their distributions shrank after the Eocene. Moreover, in the Palaeogene, species diversity of selected PPL taxa seems lower in Myanmar than in the Indian subcontinent and other regions in South-East Asia. We hypothesize that in the Eocene the Indo–Asian collision zone formed a 'hotspot' for palm diversity, which is reflected in species-rich palynofloras. However, the local palm diversity declined after the Eocene, whereas, at the global level, palm distribution was distinctly reduced between the Eocene and the present. We propose that the retreat of the palms may have occurred as early as the Eocene – Oligocene Transition (EOT), but this remains to be confirmed by the study of EOT pollen records in tropical regions.